2011
DOI: 10.1902/jop.2010.100545
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Obesity as a Modifying Factor in Patients Undergoing Non‐Surgical Periodontal Therapy

Abstract: Obesity does not seem to play a negative role by interfering in the improvement of the periodontal clinical response or decreasing circulating proinflammatory cytokine levels after periodontal treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
127
6
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(148 citation statements)
references
References 29 publications
14
127
6
1
Order By: Relevance
“…These findings are in agreement with those of Zuza et al who suggested that obesity does not interfere with periodontal therapy response, even though it is a proinflammatory and metabolically active condition (35).…”
Section: Discussionsupporting
confidence: 93%
“…These findings are in agreement with those of Zuza et al who suggested that obesity does not interfere with periodontal therapy response, even though it is a proinflammatory and metabolically active condition (35).…”
Section: Discussionsupporting
confidence: 93%
“…Recent studies evaluating the effect of periodontal treatment on inflammatory mediators in obese patients (BMI ≥ 30 kg/m 2 ) reported a significant reduction in circulating pro-inflammatory cytokines (20)(21)(22). Gonçalves et al (23) reported less of a decrease in TNF-α levels in obese patients compared with non-obese patients following non-surgical periodontal treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies (23)(24)(25)(26)(27) have examined periodontal outcomes after nonsurgical periodontal treatment (NSPT) for CP in obese patients. Although some studies reported that obesity did not affect clinical attachment gain or probing pocket depth (PPD) reduction after periodontal treatment (25,26,28), other studies showed that patients with a higher body mass index (BMI) had a poorer response to NSPT (19,24).…”
Section: Introductionmentioning
confidence: 99%